2005
DOI: 10.1249/01.mss.0000162687.18387.97
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Muscle Strength May Explain Hypoxia-Induced Decrease in Vital Capacity

Abstract: We conclude that a decrease in respiratory muscle strength may contribute to the decrease in FVC observed at high altitude.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 28 publications
2
30
0
Order By: Relevance
“…Reductions in inspiratory muscle force have been reported previously in hypobaric and normobaric hypoxia and have been correlated with reductions in FVC [19]. The reasons for the fall in FVC and TLC are most likely a combination of reduced lung compliance due to interstitial fluid accumulation and inspiratory muscle weakness as suggested by the reduced SNIP preceding HAPE (table 2) [1], [2].…”
Section: Discussionsupporting
confidence: 56%
“…Reductions in inspiratory muscle force have been reported previously in hypobaric and normobaric hypoxia and have been correlated with reductions in FVC [19]. The reasons for the fall in FVC and TLC are most likely a combination of reduced lung compliance due to interstitial fluid accumulation and inspiratory muscle weakness as suggested by the reduced SNIP preceding HAPE (table 2) [1], [2].…”
Section: Discussionsupporting
confidence: 56%
“…Similar variable results have been reported regarding respiratory muscle strength. DEBOECK et al [29] reported decreased maximum inspiratory and expiratory pressures at a simulated altitude of 4,267 m, while FORTE et al [34] showed no change in these variables at 4,300 m. The reasons for all of these conflicting results may relate to various methodological differences between the studies such as the altitude reached, the speed of ascent, and other elements of the research programme which might have altered the observed results. Unfortunately, with all of these disparities between the various studies, it is difficult to determine which are the more valid outcomes.…”
Section: Pulmonary Mechanicsmentioning
confidence: 99%
“…This change occurs within the first day and persists over time at high altitude [27,28]. Various mechanisms have been proposed to explain this change including pulmonary vascular engorgement, mild interstitial oedema [28], increased abdominal distension [26] and decreased respiratory muscle strength [29]. In contrast, total lung capacity (TLC) is increased at altitude [25,30], suggesting that residual volume is increased as well.…”
Section: Pulmonary Mechanicsmentioning
confidence: 99%
“…However, as with thoracic gas compression, few investigators have addressed the issue of air‐density dependence on FEFs obtained at high altitude (Deboeck et al. ; Basu et al. ; Fasano et al.…”
Section: Introductionmentioning
confidence: 99%